Mapping the research landscape of livestock adaptation to climate change: a bibliometric review using Scopus database (1994–2023) - Manyike, Jabulile Zamokuhle; Taruvinga, Amon; Akinyemi, Babatope E. (Frontiers in Climate, 2025)
Climate change threatens global livestock production through rising temperatures, erratic rainfall, and extreme events. Enhancing livestock system resilience is now a strategic priority for adaptation practitioners, policymakers, researchers, and other stakeholders committed to food security and rural livelihood sustainability. Although research on livestock adaptation is expanding, a comprehensive synthesis of its thematic evolution, performance, and knowledge gaps remains limited. This study addresses this gap through a bibliometric analysis of 3,217 publications from 1994 to 2023, retrieved from the Scopus database. Analytical tools such as Biblioshiny and VOSviewer were used for data processing and visualization. Findings reveal a consistent growth in research output, particularly post-2007, with the United States, China, and France emerging as leading contributors. Prominent authors include Sejian V., Wang X., and Li Y., while influential journals comprise Agricultural Systems, Journal of Animal Science, and Tropical Animal Health and Production. Thematic trends indicate a shift from early physiological studies (1994–2003) toward genetic diversity and adaptive traits (2004–2013), and more recently (2014–2023), a focus on heat stress, methane emissions, and sustainable breeding. The current research landscape emphasizes genetic adaptation, precision breeding, and climate mitigation strategies. Future studies should deepen the exploration of methane mitigation through genetic selection and feed innovations, while integrating indigenous knowledge and interdisciplinary approaches. Policy support and sustainable management practices will be critical to ensuring the long-term viability of livestock systems under a changing climate.